Evaluation of pedagogical practices from the perspective of SPAECE: elementary education - Sousa, Rosimeyre Rodrigues de (2021)
The objective of this study is to assess whether the intentional and significant pedagogical practice contributes to the improvement of the quality results of the SPAECE learning indexes, for classes in the 5th year of elementary school in the early years. Guiding questions of the study: how to evidence pedagogical practices from quantitative data? How can intentional and meaningful learning improve the quality of teaching? How can the teacher's pedagogical practice contemplate students? The methodology is a depth assessment as described by Rodrigues (2008). It will be permeated by four moments: i) document analysis; context analysis; its trajectory; and temporal and territorial dimensions, and the characteristic of the methodology is quantitative. This research shows that pedagogical practice is one of the main drivers of improving the quality of learning, which directly reflects on Public Policies for external assessment.